Pendidikan Agama Berwawasan Multikultural - Mundiro Lailatul Muawaroh (Institut Ilmu Keislaman Annuqayah, 2019)
The research delineates religious education with multicultural insight and discusses, theoretically and practically, the implementation of multicultural education in educational institutions. The research conducted a literature review as an attempt to reveal the views of experts regarding religious education with multicultural insight. Theoretically, the research found that the term multiculturalism was used differently, e.g., multiethnic and multicultural, and practically, the application of multicultural education also differed in each culture, as what happened in Canada, Germany, and the United States; So too with religious education in a broad sense. The implementation of religious education adjusted the background of each student or school. Nevertheless, although the implementation may differ, principally, religious education studied in the present research agrees to rely on cross-culture and cross-religion understanding by referring to cognitive, affective, and experience aspects.